Investigation Of Irreversible Bonding Between Polydimethylsiloxane And Printed Circuit Board For Designing Leakage-Free Dna Biochip - Ali @ Hasim, Norshah Rizal (2017)
One of the issues in designing a disposable DNA biochip based on capillary electrophoresis technology is the leakage of fluid in the microchannel though small gaps between electrodes. In this work a leakagefree and reusable biochip is designed for DNA separation and detection applications. The biochip comprises PDMS microfluidic structure fabricated with soft-lithography and copper electrodes which are engraved on FR-4 board with standard semi-automatic processes. An inhibitive layer made from photocurable diacrylate bisphenol A polymer (DABA) is used to establish irreversible bonding between PDMS and PCB substrates. Pull-off tests resulted in an average tensile strength of 287.357 kPa and standard deviation ± 23.793 kPa. These results are comparable to PDMS–PDMS bonding via conventional oxygen plasma and corona discharge. Meanwhile the leakage test showed that the microchannel could withstand pressure of more than 189 kPa which is sufficiently high for most biochip applications. Finally experiments performed on single DNA band produced by using PCR and multiple bands from standard DNA ladders indicated that the proposed design can accurately separate DNA fragments with current sensitivity consistently higher than 100 nA and at electric field strength of 20V/cm. Comparing to the previous design that used clips to mechanically clamp PDMS and PCB substrates, the new approach effectively seals the device, thus preventing leakage of liquid from the sensor matrix. This together with the electrochemically inert characteristics of the photopolymer inhibitor, open up possibilities in designing a truly portable bio-sensing device.